1982
DOI: 10.1063/1.442841
|View full text |Cite
|
Sign up to set email alerts
|

Reactive scattering and electron detachment in collisions of halogen negative ions with isotopic hydrogen molecules

Abstract: Total cross sections for reactive scattering and collisional electron detachment have been measured for collisions of F− and Cl− with H2, D2, and HD. The collision energy extends from below the energetic thresholds for the processes studied up to a laboratory energy of about 300 eV. Reactive scattering is found to be the dominant inelastic channel for the case of the F− projectile. Isotope effects are observed in all cross sections. Electron detachment of F− is found to occur by two distinct mechanisms. A stri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

1985
1985
1999
1999

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 25 publications
2
5
0
Order By: Relevance
“…Thus, there is a large barrier (> 1 eV) to Hproduction for these reactants, in contradistinction to what is observed for the 0-projectile. It is interesting to note that the cross sections in this region increase in the order D 2 : H 2 : HD, which is similar to that observed previously by Huq et al 26 for Cl--H2' D 2 , and HD. The most remarkable feature of uAE) presented in Fig.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Thus, there is a large barrier (> 1 eV) to Hproduction for these reactants, in contradistinction to what is observed for the 0-projectile. It is interesting to note that the cross sections in this region increase in the order D 2 : H 2 : HD, which is similar to that observed previously by Huq et al 26 for Cl--H2' D 2 , and HD. The most remarkable feature of uAE) presented in Fig.…”
Section: Resultssupporting
confidence: 89%
“…Between 3 and 10 eV, (1.,(E) exhibits structure which is believed to be associated with detachment accompanied by reactive scattering, e.g., This suggestion is supported by the observation that the structure in u., (E) in this energy range is typical of endothermic ion-molecule reaction cross sections. Similar structure in u., (E) has been observed previously by Huq et al 26 for the reactants F--H 2 . In those studies it was concluded that detachment with reactive scattering occurs as a companion to the ion-molecule reaction; thus the low energy structure observed in the present study is attributed to a similar mechanism.…”
Section: Resultssupporting
confidence: 87%
“…An alternative method for obtaining a gas-phase acidity is to measure the threshold energy for an endoergic proton transfer reaction. In this work, reaction 1 is studied using guided ion beam tandem mass spectrometry The measured 0 K reaction threshold energy for reaction 1, E 0 , is equal to the reaction enthalpy, Δ r H 0 , in the absence of any potential barriers along the reaction path or any dynamical barriers hindering proton transfer.…”
Section: Introductionmentioning
confidence: 99%
“…If we invert Eq. (5) for f, tions are known for the systems Cl +Hz via Huq et al [12] and Cl +H via a calculation by Gauyacq [13]. This latter calculation has been experimentally verified in this laboratory for E =5 eV, but the results are yet to be published.…”
Section: Specificallymentioning
confidence: 96%
“…[12,13] for Cl +Hz and H, a "transmission function, " which incorporates the target thickness and is therefore dependent upon both energy and number density, can be defined as follows: For relative collision energies above about 1 eV, the uncertainty in the dissociation fraction can account for about a 15% error in the cross section for both reactants; below 1 eV, this error is reduced to less than 5% for the system S +H. Another concern is the overlap between the anion and H or Hz beams (i.e.…”
Section: Specificallymentioning
confidence: 99%